Modelling of food product cutting - Guts, Viktor; Gubenia, Oleksii; Stefanov, Stefan; Hadzhiyskiy, Vilygelym (My University, 2010)
There are lead theoretical experimental researches on the basis of which is developed the simple in application technique for research of movement of an edge in a layer of a product. The mathematical model which adequately describes process is also developed. The technique is applied at research of bread cutting by results of which optimum cutting conditions are certain.
Keywords: bread; cutting; modelling; хліб; різання; моделювання; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра екології та екоменеджменту